La diplomacia de Smart Cities: el caso de la ciudad de Barcelona - Cerqueira, Olga María (2019)
This research is based on the diplomacy of Barcelona City and the configuration of a hegemonic discourse on Smart City, with repercussions at a local and global level. The emphasis is on interactions and coalitions in network with other cities, establishing that Barcelona, as Smart City, projects an image of a leading and dynamic city, under construction and continuous growth that exerts a relational leadership, besides aims conformation of networks and structures where cities and their actors are connected learning and exchanging experience, reaching international positioning, economic activity, and agreements, as a reflection of a narrative sustained in openness, flexibility and inclusion, that precisely justifies the participation and political action of Barcelona as a city in global multilevel governance.